2020
DOI: 10.1186/s12889-019-8109-y
|View full text |Cite
|
Sign up to set email alerts
|

Arts, mental distress, mental health functioning & life satisfaction: fixed-effects analyses of a nationally-representative panel study

Abstract: Background Arts engagement within communities is ubiquitous across cultures globally and previous research has suggested its benefits for mental health and wellbeing. However, it remains unclear whether these benefits are driven by arts engagement itself or by important confounders such as socio-economic status (SES), childhood arts engagement, previous mental health, personality, or self-selection bias. The aim of this study is to use fixed effects models that account for unidentified time-constant confoundin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 33 publications
5
56
0
Order By: Relevance
“…International migration has strongly manifested itself to historic highs. Many studies regarding international migration have been conducted from different perspectives [32,[35][36][37][38][39][40][41][42][43][44]. Among the discussions, there is an increased interest in the issues of social capital and network resources in migration and integration research [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…International migration has strongly manifested itself to historic highs. Many studies regarding international migration have been conducted from different perspectives [32,[35][36][37][38][39][40][41][42][43][44]. Among the discussions, there is an increased interest in the issues of social capital and network resources in migration and integration research [8][9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the first large population-based study to investigate whether the association between CCE (attending cultural events or visiting museums and heritages sites) Open access Open access show that engagement in cultural assets was consistently and positively associated with subsequent life satisfaction and mental health functioning and negatively associated with mental distress. 3 Importantly, this paper found that such associations were independent of individuals' demographic background, socioeconomic characteristics and regional locations. In particular, our models show that every one SD increase in CCE is associated with higher life satisfaction and mental health functioning (by 0.06-0.13 SD) and lower mental distress (by 0.05-0.09 SD).…”
Section: Discussionmentioning
confidence: 68%
“…Despite this, a number of previous studies have already confirmed that CCE can be causally linked to well-being through randomised interventions, 1 2 and the generalisability of such findings has been suggested through causal inference analyses of longitudinal data in other papers. 3 As another limitation, the Index of Multiple Deprivation is composed of various components (eg, living environment, income and employment deprivation) as a proxy of neighbourhood effect. However, it will be important to understand from future studies how other neighbourhood characteristics (eg, demographic structure and population density) may also influence the engagement level.…”
Section: Open Accessmentioning
confidence: 99%
“…Among the many possible receptive or creative interventions (attending performances, making or viewing visual art or music, etc), visually engaging artwork or visiting museums and galleries have increasingly been employed in partnership with public health initiatives, and healthcare providers in several countries have started to prescribe such activities as psychological health interventions (Camic & Chatterjee, 2013;Chatterjee & Noble, 2017;Packer & Bond, 2010;Thomson et al, 2018;Todd et al, 2017). Among the various effects, empirical evidence has shown that on-site art interactions have been particularly associated with decreased loneliness (Todd et al, 2017;Tymoszuk et al, 2019Tymoszuk et al, , 2020, improved mental health (symptoms of anxiety and depression; Clayton & Potter, 2017;Hansen et al, 2015;Roberts et al, 2011), and increased mood and subjective wellbeing (Bennington et al, 2016;Binnie, 2010;Davies et al, 2016;Hansen et al, 2015;Ho et al, 2015;Karnik et al, 2014;Roberts et al, 2011;Wang et al, 2020). For example, similar to the interventions that will be explored in this paper, Clow and Fredhoi (2006) asked individuals to take a 35-minute visit to an art gallery on their lunch break and found that even short exposures lead to significantly lower self-reported stress (~2.4 points on a pre-/post-visit 10-point scale)…”
Section: Background-(online) Art As a Wellbeing Interventionmentioning
confidence: 99%